Concentration Test for Ferrous Sulfate (FeSO4) and Thiamin in Murashige and Skoog Medium on The Orchid Sub-Culture Dendrobium SP By In-Vitro - Nadia Ratna Sari; Elfi Indrawanis; Pebra Heriansyah (Postgraduate, University of Mataram, 2023)
The Dendrobium orchid is one type with special features and many variations. This study aims to determine the administration of various concentrations of ferrous sulfate (FeSO4) and Thiamin to Dendrobium sp orchid explants on Murashige And Skoog media. The design used in this study was a Factorial Completely Randomized Design (CRD) consisting of 2 treatment levels (F = FeSO4 and T = Thiamin) with three replications. Namely: F0 (Without FeSO4), F1 (FeSO4 26.8 mg/l ), F2 (FeSO4 27.8 mg/l), F3 (FeSO4 28.8 mg/l), and T0 (Without Thiamin), T1 (Thiamin 0.1 mg/l), T2 (Thiamin 0.2 mg/l) l), T3 (Thiamin 0.3 mg/l). Based on the study results, by giving various concentrations of ferrous sulfate (FeSO4) had a single effect on the shoots quantity parameters with the best treatment found in treatment with an average shoots quantity (.03 ea), F3 for shoot height parameters (1.37 cm), for the total leaves (6.14), for the roots quantity (5.17), and root length were found in treatment with an average of 1.29 cm on the Dendrobium sp. Orchid explants. For the treatment of various concentrations of Thiamin, the single effect on the number of shoots with the best treatment was found at an average (3.44 ea), for the shoot height parameter (0.98 cm), and for the leaves quantity (6.14 ea), for the root length parameter (1.28 cm). The interaction significantly affected the observed parameters, namely the number of shoots with treatment (giving FeSO4 28.8 mg/l and Thiamin 0.3 mg/l) with an average shoot quantity of 1.71 (ea).